Efeito dos contrastes radiológicos diatrizoato de sódio e lopamidol na função e morfologia renal de ratos Wistar de ambos os sexos uni-nefrectomizados e em restrição hídrica - Rocha, Valéria Cristina da (2007)
Patients undergoing contrast media procedures can develop nephrotoxicity. The renal damage is higher when predisposing factors are present as debetes mellitus, type and dose of radiocontrast. Low-osmolar contrast media are less nephrotoxic than the high-osmolar one. Nevertheless they can not avoid nephropathy. Female sex has been considered as an independent risk factor for contrast nephropathy. Experimental studies try to elucidate the pathogenisis and characteristics of this nephropathy. To induce radicontrast nephrotoxicity in animals with normal renal function is difificults and it is necessary to expose them to multiples insults. The present study aimed to evaluate the renal damage, through histopathology and serum creatinine and BUN levels, caused by diatrizoate and lopamidol used in uninephrectomized and dehydrated female and male Wistar rats. It was used 46 rats (24 female/ 22 male), divided in 8 groups: saline - IA (female) e IB (male); sham - IIA (female) e IIB (male); diatrizoate (IIIA - female e IIIB - male) and lopamidol (female - IVA / male - IVB). Intravascular injections of 7,8 mL/Kg (2,9mg I/Kg) contrasts (2.9 mg I/Kg) and saline were administered. Blood samples collections, euthanasia and necropsia were done 3 hours after drugs injections. Renal samples were collected to light microscopic descriptive and semi-quantitative studies. In female rats, diatrizoate produced rise in seric creatinine. Comparing lopamidol and diatrizoate contrasts, there was no diference between them. In male rats, 3 hours after injection of contrasts and saline, there was no difference in rise of creatinine levels of groups IVB and IIIB. By the gender factor study, there was no difference in creatine levels between genders after diatrizoate. Males were more affected after lopamidol injection. Vacuolization of the proximal tubular epithelial cells was produced. Control groups: IA, IIA, IIIB showed normal renal structure. IIIA and IVA groups revealed accentuated vacuolization and gpoups IB and IIIB, light vacuolization. IVB group showed mild vacuolization. Comparing gender, histopathologic findings were most proeminent in females (IIIA, IVA groups) and there was no correlation between histopathology and biochemical findings. The results of the study support that patients should be evaluated for kidney function, when submitted to to radiological procedures using theses agents, to prevent renal complicatiions as the radiocontrast nephropathy